Does the presence of placental basal plate myometrial fibres increase the risk of subsequent morbidly adherent placenta: a case–control study. (11th August 2015) - Miller, ES; Linn, RL; Ernst, LM
Abstract : Objective: Antenatal diagnosis of morbidly adherent placenta has been shown to improve outcomes, but existing predictors lack sensitivity. Our objective was to determine whether the presence of myometrial fibres attached to the placental basal plate (BPMYO) in an antecedent pregnancy is associated with subsequent morbidly adherent placenta. Design: A case–control study. Setting: Departments of Obstetrics and Gynecology and Pathology, Northwestern University, Chicago, IL, USA. Sample: Women who had at least two pregnancies with placental pathological evaluation. Methods: Cases were defined as women with evidence of morbidly adherent placenta (both clinically and pathologically) in their most recent pregnancy whereas women without evidence of morbidly adherent placenta served as controls. Pathological specimens of placentas from previous pregnancies were evaluated for BPMYO. The presence of BPMYO on a previous placenta was evaluated to determine whether it could be used to improve the antenatal diagnosis of morbidly adherent placenta. Results: Of the 25 cases of morbidly adherent placenta, 19 (76%) had BPMYO present on their previous placenta compared with 41 (41%) of controls (odds ratio 4.8, 95% CI 1.8–13.0). Adding BPMYO to a regression including other risk factors for morbidly adherent placenta (i.e. maternal age, number of previous caesarean sections, placenta praevia, previous multiple gestation, any previous curettage, and ultrasonographic suspicion of placenta accreta) significantly improved the sensitivity of antenatal diagnosis of morbidly adherent placenta (61% versus 39%, P < 0.001) without a change in specificity (97% versus 97%, P = 1.00). Conclusion: BPMYO on previous placental pathology is associated with an increased risk of morbidly adherent placenta in a subsequent pregnancy. These findings may shed light on the pathophysiology of accreta and inform future research on predictors of accreta. Tweetable abstract: Previous basal plate myometrium improves the ability to detect subsequent morbidly adherent placenta. Tweetable abstract: Previous basal plate myometrium improves the ability to detect subsequent morbidly adherent placenta.